Fullerene and Tungsten Oxide Nanostructures-based Electrocatalysts for All-Vanadium Redox Flow Batteries - El Diwany, Farah Ahmed (AUC Knowledge Fountain, 2021)
The vanadium redox flow battery (VRFB) is one of the most promising long-term energy storage solutions mainly due to its long service life and the independence of its energy capacity on power rating and vice versa. However, its relatively high capital cost limits its widespread deployment. Economic analysis reveals that a high-power density VRFB with decreased cell stack size can dramatically reduce the cost. The energy efficiency of a VRFB primarily depends on the kinetics of vanadium redox reactions that take place in the stack. Therefore, studying the effect of surface chemistry of electrodes on the kinetics of each half-cell reaction is important. Accordingly, this thesis aims to enhance the kinetics of the redox reactions at the negative and positive electrodes. The thermal treatment of carbon cloth (CC) electrodes was studied and was found to improve the kinetics of both half-cell reactions. The incorporation of C76 particles further enhanced the kinetics of the VO2+/VO2+ redox reaction. A 99.5% and 97% decrease in the VO2+/VO2+ electron transfer resistance was achieved, compared to thermally treated CC (TCC) and untreated CC (UCC). Less chlorine evolution and higher stability upon cycling were also achieved for C76, showing that treatment was not only unnecessary but also unsatisfactory in terms of cyclic stability. WO3.0.33H2O/W32O84 (hydrated tungsten oxide, HWO) was fabricated by a hydrothermal method and used primarily for the V2+/V3+ redox reaction. It exhibited superior kinetics compared to TCC. In addition to inhibiting the parasitic hydrogen evolution reaction, HWO was found to enhance the stability of the negative electrode relative to TCC. As for the VO2+/VO2+ reaction, a nanocomposite of HWO-50% C76 was found to not only decrease the charge transfer resistance and enhance the electrode stability, but also further inhibit chlorine evolution, relative to UCC, TCC and C76. This shows the great potential of HWO-50% C76 and HWO as electrocatalysts for VO2+/VO2+ and V2+/V3+ redox reactions, respectively, towards lower-cost VRFBs.